Revealing Seed Coat Colour Variation and Their Possible Association with Seed Yield Parameters in Common Vetch (Vicia sativa L.) - Gulgun Yildiz Tiryaki; Abdullah Cil; Iskender Tiryaki (International Journal of Agronomy)
The seed coat colour variation of 70 common vetch genotypes were determined by using uniform colour scale (L⁎a⁎b⁎) and their possible correlation with seed yield parameters including the number of pods per plant, the number of seeds per pod, pod dimension, and seed yield (kg/da) was determined. The results revealed presence of highly significant (p<0.01) variations for both the seed yield and the seed coat colour parameters measured. The number of pods per plant, the number of seeds per pod, and seed yield ranged from 5.8 to 16.03, from 5.2 to 7.66, and from 143.37 to 531.1, respectively. The lightness value varied from 19.00 to 40.28 while chromaticity a⁎ and b⁎ values ranged from −0.16 to 8.99 and from 0.79 to 22.11, respectively. The highest correlation coefficients were determined between b⁎ and L⁎ (r=0.73), and a⁎ and L⁎ (r=0.55). The seed coat colour traits and seed yield parameters generally showed weak negative correlations. Seed yellowness (b⁎) and seed yield had correlation coefficient of −0.25, while correlation between L⁎ and seed yield was determined as −0.23. The results indicated that lightness and yellowness of seed coat may be used as an important parameter to prescreen high yield genotypes of common vetch.